(untitled) (Ustozlar uchun, 2026)
This paper explores contemporary innovative approaches to enterprise strategic management within the framework of sustainable development. The study emphasizes the incorporation of innovation management practices, digital transformation processes, ESG principles, and green economy concepts into corporate strategies. Using statistical data from Uzbekistan covering the period 2018–2024, along with SWOT analysis and forecast extrapolations for 2025–2030, the research identifies major development trends, existing constraints, and strategic priorities for sustainable enterprise growth. The results indicate that innovation-oriented strategic management plays a crucial role in strengthening enterprise competitiveness, adaptability, and long-term sustainability, especially in economies undergoing structural transformation. The findings are intended to support academic research, public policy formulation, and practical decision-making in the field of strategic and sustainable development.